Office Facilities Work Motivation And Discipline Determining Village Apparatus Performance: Fasilitas Kantor Motivasi Kerja Dan Disiplin Menentukan Kinerja Perangkat Desa - Ni Luh Meilia Setyani; Gunawan Wibisono; Komang Sudarsana (Indonesian Journal of Law and Economics Review, 2026)
General Background Village apparatus personnel hold a strategic role in administering local governance, public services, and rural development. Specific Background At the Blimbingsari Village office in Jembrana, administrative operations face significant challenges characterized by delayed attendance, suboptimal utilization of available workspaces, and low personnel enthusiasm. Knowledge Gap Most existing human resource literature evaluates corporate or educational environments, leaving a limited understanding regarding the simultaneous combination of physical workspaces, personal drive, and professional compliance within rural governance settings. Aims This study evaluates how office facilities, work motivation, and work discipline concurrently and partially determine the operational performance of Blimbingsari Village officials. Results Based on a quantitative analysis of 30 village officials utilizing multiple linear regression, the findings demonstrate that office facilities, work motivation, and work discipline collectively and individually yield a positive and significant role in dictating the operational output of the apparatus. Novelty This research distinctly integrates these three operational and behavioral variables simultaneously to evaluate public service delivery specifically within a rural village government context. Implications Local government leaders must actively provide adequate administrative equipment, cultivate professional enthusiasm, and enforce consistent regulatory compliance to guarantee high-quality public service delivery and optimal rural human resource management. Highlights Adequate physical workspaces significantly dictate rural administrative operational quality. Consistent professional compliance guarantees timely public service delivery. High personal enthusiasm concurrently drives local government personnel productivity. Keywords Office Facilities; Work Motivation; Work Discipline; Village Apparatus Performance; Human Resource Management